Self-injurious thoughts and behaviours as the reason for contact to Norwegian emergency primary care centres: an observational study - Anita Hunsager; Fredrik A. Walby; Vivian Midtbø; Tone Morken; Valborg Baste; Ingrid Hjulstad Johansen (Scandinavian Journal of Primary Health Care)
Objective To describe and compare contacts regarding self-injurious thoughts and behaviours to other contacts to emergency primary care.Design Observational study.Setting A sentinel network of seven emergency primary care centres throughout Norway.Subjects Initial contacts regarding patients 10 years and older during 12 consecutive months (11/2021–10/2022).Main outcome measures Contacts due to self-injurious thoughts and behaviours.Results Self-injurious thoughts and behaviours were the reason for contact for 0.6% (n = 478) of initial contacts for patients aged 10 years or older (n = 77 344). When compared to other contacts, self-injurious thoughts and behaviours were associated with female gender, younger age, occurrence during evening and nighttime, higher urgency, and more physician consultations and call-outs. Of contacts about self-injurious thoughts and behaviours, 58.2% were regarding thoughts and 41.8% about behaviours, and in 75.0% a history of similar contacts was recorded. Contacts regarding thoughts often concerned threats (30.6%) and were more often handled by telephone advice than contacts regarding behaviours. Contacts regarding behaviours with suicidal intent were associated with higher urgency and more physician call-outs than contacts regarding non-suicidal behaviours.Conclusion Self-injurious thoughts and behaviours are rare reasons for contact to emergency primary care but are assessed as more urgent than other contact reasons and trigger more extensive medical help. Many of the patients are known to the service through a history of similar contacts.Implications The infrequency and severity of these encounters might necessitate training, decision support and procedures to compensate for the health care personnel’s limited exposure.